On the Secrecy of Interference-Limited Networks under Composite Fading Channels - Alves, Hirley; Lima, Carlos H. M. de [UNESP]; Nardelli, Pedro. H. J.; Souza, Richard Demo; Latva-aho, Matti (Ieee-inst Electrical Electronics Engineers Inc, 2015)
This letter deals with the secrecy capacity of the radio channel in interference-limited regime. We assume that interferers are uniformly scattered over the network area according to a Point Poisson Process and the channel model consists of path-loss, log-normal shadowing and Nakagami-m fading. Both the probability of non-zero secrecy capacity and the secrecy outage probability are then derived in closed-form expressions using tools of stochastic geometry and higher-order statistics. Our numerical results show how the secrecy metrics are affected by the disposition of the desired receiver, the eavesdropper and the legitimate transmitter.
Keywords: Composite channel; secrecy capacity; secrecy outage probability; stochastic geometry